Effect of Cr3+ doping on structural and optical properties of Eu3+ doped LaVO4 phosphor - Rai E.; Yadav R.S.; Kumar D.; Singh A.K.; Fulari V.J.; Rai S.B. (My University, 2025)
In this work, the Eu3+, Cr3+ doped and co-doped LaVO4 phosphors have been prepared through a high temperature solid-state reaction method. The powder XRD patterns of phosphors are very sharp and intense, which reflects a highly crystalline nature of phosphors. The XRD data were also refined by a Rietveld refinement method. The particle size of the phosphor samples lies in the sub-micron to micron range. The existence of La, Eu, Cr, V and O elements was verified by EDS spectra. The FTIR spectra show various absorption bands due to different vibrating groups. The optical band gap of the phosphor decreases on increasing concentration of Cr3+ ion. The photoluminescence excitation spectra of Eu3+, Cr3+ co-doped LaVO4 phosphor exhibit bands due to Eu3+ and Cr3+ ions. The Eu3+ doped LaVO4 phosphor exciting at 393 and 316 nm wavelengths gives intense red color at 614 nm due to the 5D0 → 7F2 transition of the Eu3+ ion. When the Cr3+ ion is co-doped in the Eu3+ doped LaVO4 phosphor the emission spectra contain emission bands due to Eu3+ and Cr3+ ions. The emission intensity of Eu3+ doped phosphor reduces due to energy transfer from Eu3+ to Cr3+ ions in presence of Cr3+ ions upon 393 and 386 nm excitations. The lifetime of the 5D0 level of Eu3+ ions decreases in the Eu3+, Cr3+ co-doped LaVO4 phosphor, which also reflects the energy transfer. The Eu3+, Cr3+ co-doped LaVO4 phosphor also produces a large amount of heat upon 980 nm excitation. Thus, the Eu3+, Cr3+ co-doped LaVO4 phosphors may be used for LEDs, solid state lighting and heat generating devices. © 2023 The Royal Society of Chemistry.